Digitalization Agriculture Support Resistance National In Review From Please The 3RD Pancasila - Sakdiyah, Nikmatus (Jurnal Pallangga Praja (JPP), 2025)
Food security is a condition for satisfying the quality and quantity of food needs for households in a safe, equitable, and affordable manner. The relationship between population, natural resources, and the economy will realize harmonization that will realize food security and community welfare and have a positive impact on Indonesia's national resilience. This paper is the result of a review of various research results and literature compiled from the formulation of problems regarding how to realize agricultural digitalization strategies to support national resilience and whether agricultural digitalization is in line with the values of Pancasila 3rd precept. This paper aims to analyze agricultural problems through digitalization to support national resilience, contribute ideas to solve agricultural problems through agricultural digitalization to support national resilience, provide an overview of the realization of the 3rd precept of Pancasila through agricultural digitalization. This paper is prepared using a qualitative descriptive method. The analysis of data obtained from secondary data provides a description of the conditions of agricultural digitalization in Indonesia in the form of a narrative description. Smart farming provides agricultural solutions as an agricultural management concept strategy that utilizes the sophistication of digital technology with Artificial Intelligence (Al), agricultural tools and machinery, sensors, mechanization, and the Internet that can make it easier for farmers to do their work. Agricultural digitalization realizes food security for the Indonesian nation and encourages national resilience. Agricultural digitalization through smart farming provides solutions to agricultural problems in Indonesia. The agricultural digitalization strategy is designed to be implemented starting from upstream, cultivation, and downstream. Agricultural digitalization through smart farming fosters a sense of farmer unity and is in line with the 3rd precept of Pancasila.